2009
DOI: 10.1017/s096012950999017x
|View full text |Cite
|
Sign up to set email alerts
|

On the expressive power of recursion, replication and iteration in process calculi

Abstract: In this paper we investigate the expressive power of three alternative approaches to the definition of infinite behaviours in process calculi, namely, recursive definitions, replication and iteration. We prove several results discriminating between the calculi obtained from a core CCS by adding the three mechanisms mentioned above. These results are derived by considering the decidability of four basic properties: termination (that is, all computations are finite); convergence (that is, the existence of a fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 10 publications
(15 reference statements)
3
48
0
Order By: Relevance
“…In HOCORE such an upper bound does not exist. This was essential for obtaining the decidability result; for this, we appealed to the approach developed in [9], which relies on the theory of well-structured transition systems [8]. As far as we are aware, this approach for expressiveness has not previously been used in the higher-order setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In HOCORE such an upper bound does not exist. This was essential for obtaining the decidability result; for this, we appealed to the approach developed in [9], which relies on the theory of well-structured transition systems [8]. As far as we are aware, this approach for expressiveness has not previously been used in the higher-order setting.…”
Section: Discussionmentioning
confidence: 99%
“…In sharp contrast with HOCORE, termination in HO −f is decidable. This result is obtained by appealing to the theory of well-structured transition systems [8], following the approach used in [9].…”
Section: Similarly As Hocore Homentioning
confidence: 99%
See 1 more Smart Citation
“…An absolute expressiveness result establishes that a process calculus can or cannot express a particular process or a particular type of processes. It is then, e.g., shown that a process calculus is, or is not, Turing-powerful [11]. More refined forms of absolute expressiveness may also be exploited to compare the relative expressiveness of two process calculi, by showing that a certain type of process can be expressed in the one calculus but not in the other (see, e.g., [5,7,4]).…”
Section: Interactive Turing Machines Van Leeuwen and Wiedermann Propmentioning
confidence: 99%
“…No other direct implications among these criteria exist. For instance, in (Busi et al 2009) it is proved that CCS (Milner 1989) with replication instead of recursion is Turing complete according to Criterion 2 but not according to Criteria 1 or 3.…”
Section: Turing Completeness Of Bgfmentioning
confidence: 99%